2005
DOI: 10.1038/sj.jhh.1001971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of target organ lesion detection (assessment of microalbuminuria and echocardiogram) in cardiovascular risk stratification and treatment of untreated hypertensive patients

Abstract: European guidelines indicate the importance of the evaluation of global cardiovascular risk (CVR) to determine the management of the hypertensive patients (EH). However, in primary care, the diagnostic work-up (PCD) only includes the metabolic risk factors. The aim of this study was to assess the importance of microalbuminuria (MA) and echocardiogram (ECHO) in the process of risk stratification, and the number of patients to be treated with drugs at diagnosis. In total, 155 nontreated EH were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…32 For example, the measurement of microalbuminuria, is an easy and low-cost determination, according to 2003 ESH/ESC guidelines, and it seems to be a cost-effective screening test to avoid the underestimation of the CVR. 33 This underestimation of the risk probably implies that hypertensive patients could be frequently undertreated, what may have a critical influence in a poor BP control, mainly in high-risk groups. Moreover, these high-risk patients could also be denied of other beneficial interventions such as statins 34 on the basis of underestimation of the risk.…”
Section: Test For Sex and Bmi Distributionmentioning
confidence: 99%
“…32 For example, the measurement of microalbuminuria, is an easy and low-cost determination, according to 2003 ESH/ESC guidelines, and it seems to be a cost-effective screening test to avoid the underestimation of the CVR. 33 This underestimation of the risk probably implies that hypertensive patients could be frequently undertreated, what may have a critical influence in a poor BP control, mainly in high-risk groups. Moreover, these high-risk patients could also be denied of other beneficial interventions such as statins 34 on the basis of underestimation of the risk.…”
Section: Test For Sex and Bmi Distributionmentioning
confidence: 99%
“…The only study we found about risk stratification in patients with hypertension using the 2003 guidelines found a somewhat more important role of echocardiography. 13 Differences in the determination of urinary albumin excretion (strips versus nephelometry), in the definition of left ventricular hypertrophy on ECG (adding Cornell Voltage product in our study) and in the prevalence of left ventricular hypertrophy on echocardiography are reasonable explanations for these discrepant findings.…”
Section: Discussionmentioning
confidence: 60%
“…It is difficult to explain the substantial differences in the prevalence of left ventricular hypertrophy between different studies. [9][10][11][12][13] Patient selection from a hypertension clinic in previous studies compared to a general medical outpatient clinic in the present study may be partially responsible. However, the prevalence of echocardiographic left ventricular hypertrophy in the present study is consistent with that recently reported in a general population sample.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Even high-normal albuminuria (10-20 mg/l) is an independent and early CVD risk factor [41]. Furthermore, patients with an albumin-to-creatinine ratio of 0.65 to 2.0 mg/mmol (a ratio of 2.0 mg/mmol indicates microalbuminuria) have more than twice the cardiovascular risk of patients with normal urinary albumin excretion rate (UAER) [42,43].…”
Section: Markers Of Renal Function: Proteinuriamentioning
confidence: 98%